Psychiatry : a very short introduction - Burns, Tom (Oxford University Press, 2006)
Psychiatry is now a highly visible activity - care in the community, compulsion, suicide, drug and alcohol abuse mean that few people are not touched by it. Indeed one in four of us will consult a psychiatrist in our life time. This book explains what psychiatry is, and what it is not. It starts with the identification of the major mental illnesses and why they are no longer considered just variations of 'normality'. It charts the rise of the Asylum and its demise with the developments of Care in the Community, and the flourishing of psychoanalysis and its later transformation into more accessible psychotherapies.